Aksiologi dalam Perspektif Islam - Ahmad, sulaeman; Syatar, Abdul; Nurbaety, Andy (Sulesana: Jurnal Wawasan Keislaman, 2025)
The study of philosophy cannot be separated from the discussion of humans. Because, humans are the determinants of the good and bad judgments of other humans. In terms of values ​​in philosophy, it can be found in the branch of philosophy, namely axiology. Axiology is a branch of philosophy that discusses values, in other words, axiology is a field of philosophy that explains the application of a science that has good and bad values, the results of that knowledge. The research method used is a literature study, which emphasizes various literatures that are in accordance with the object being studied. Axiology in the Islamic perspective states that religion gives birth to science. So science can be said to be part of religion itself, because the Prophet Muhammad SAW requires humans to seek knowledge. And the purpose of religion is to seek the pleasure and truth of Allah SWT. Science is part of Islam and the function of science is to provide guidance, solutions, as a deliverer from ignorance. Science gives birth to values, ethics and aesthetics, while Islam is an umbrella for the birth of ontology, epistemology, and axiology.